LEAP-2: An Emerging Endogenous Ghrelin Receptor Antagonist in the Pathophysiology of Obesity - Lu, Xuehan; Huang, Lili; Huang, Zhengxiang; Feng, Dandan; Clark, Richard J.; Chen, Chen (Frontiers in Endocrinology, 2021)
Liver-expressed antimicrobial peptide 2 (LEAP-2), originally described as an antimicrobial peptide, has recently been recognized as an endogenous blocker of growth hormone secretagogue receptor 1a (GHS-R1a). GHS-R1a, also known as ghrelin receptor, is a G protein-coupled receptor (GPCR) widely distributed on the hypothalamus and pituitary gland where it exerts its major functions of regulating appetite and growth hormone (GH) secretion. The activity of GHS-R1a is controlled by two counter-regulatory endogenous ligands: Ghrelin (activation) and LEAP-2 (inhibition). Ghrelin activates GHS-R1a on the neuropeptide Y/Agouti-related protein (NPY/AgRP) neurons at the arcuate nucleus (ARC) to promote appetite, and on the pituitary somatotrophs to stimulate GH release. On the flip side, LEAP-2, acts both as an endogenous competitive antagonist of ghrelin and an inverse agonist of constitutive GHS-R1a activity. Such a biological property of LEAP-2 vigorously blocks ghrelin’s effects on food intake and hormonal secretion. In circulation, LEAP-2 displays an inverse pattern as to ghrelin; it increases with food intake and obesity (positive energy balance), whereas decreases upon fasting and weight loss (negative energy balance). Thus, the LEAP-2/ghrelin molar ratio fluctuates in response to energy status and modulation of this ratio conversely influences energy intake. Inhibiting ghrelin’s activity has shown beneficial effects on obesity in preclinical experiments, which sheds light on LEAP-2’s anti-obesity potential. In this review, we will analyze LEAP-2’s effects from a metabolic point of view with a focus on metabolic hormones (e.g., ghrelin, GH, and insulin), and discuss LEAP-2’s potential as a promising therapeutic target for obesity.